THE NEEDS ANALYSIS OF DEVELOPING INTERACTIVE E-MODULE IN SCIENCE LEARNING FOR JUNIOR HIGH SCHOOL - Mardhiah, Hayatul; Oktavia, Rani (Department of Science Education, 2025)
The 21st century learning is a learning transition in which the developed curriculum requires schools to be able to change the learning approach from teacher centered to student centered. This is supported by the principle of an Kurikulum Merdeka where to achieve learning outcomes it is necessary to use information and communication technology devices in the learning process. One effort that can be made to support educational goals in the 21st century is the development of interactive e-modules in science learning. The purpose of this study was to determine the need for the development of interactive e-modules in junior high school science learning. The method used in this study is qualitative using a descriptive approach. The instruments used in collecting data were observation sheets, interview questionnaires and student characteristics questionnaires. The results of this study are (1) Science learning in schools is still conducted by teacher centered approach; (2) student have low interest and motivation in learning science; (3) There are less innovative teaching materials used to support the science learning process. The conclusion from this study is the need to develop teaching materials in the form of Interactive E-Modules in science learning so that it is expected that science learning can be conducted by student centered approach and increase student interest and motivation which has an impact on improving learning outcomes.